2017
DOI: 10.1016/j.omtn.2017.09.011
|View full text |Cite
|
Sign up to set email alerts
|

A New Long Noncoding RNA ALB Regulates Autophagy by Enhancing the Transformation of LC3BI to LC3BII during Human Lens Development

Abstract: Autophagy is essential in lens organelle degradation. This study aimed to seek potential autophagy-associated long noncoding RNAs (lncRNAs) and their relative mechanisms in human lens development using the “fried egg” lentoid body (LB) generation system. The expression pattern of LC3B in differentiating LBs was similar to that in developing a mouse lens in vivo. Among the massive lncRNAs expressed with a significant difference between induced pluripotent stem cells (iPSCs) and LBs, lncRNA affecting LC3B (ALB),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Previous studies have indicated that autophagy may play an important role in both lens development and cataract formation (Andley & Goldman, ; Chen et al, ; Morishita et al, ; Sagona, Nezis, & Stenmark, ; Wignes, Goldman, Weihl, Bartley, & Andley, ). Our previous study on this topic found that autophagy was involved in the differentiation process of LBs (Fu et al, ), which is partially consistent with its function in human lens development. To investigate the role of autophagy in ARCs as well as the clouding process of LBs, we analyzed the expression of autophagy marker LC3B in both human lens capsules from ARC patients and in LBs at different time points.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Previous studies have indicated that autophagy may play an important role in both lens development and cataract formation (Andley & Goldman, ; Chen et al, ; Morishita et al, ; Sagona, Nezis, & Stenmark, ; Wignes, Goldman, Weihl, Bartley, & Andley, ). Our previous study on this topic found that autophagy was involved in the differentiation process of LBs (Fu et al, ), which is partially consistent with its function in human lens development. To investigate the role of autophagy in ARCs as well as the clouding process of LBs, we analyzed the expression of autophagy marker LC3B in both human lens capsules from ARC patients and in LBs at different time points.…”
Section: Resultssupporting
confidence: 67%
“…To address this gap, our group recently developed a new lens regeneration method-we have termed it the "fried egg" methodduring which LBs derived from human iPSCs showed transparent morphology and not only expressed lens-specific markers but also exhibited basic optic characteristics (Fu et al, 2017a). Moreover, the LB differentiation process partially mimicked human lens development (Fu et al, 2017a;Fu et al, 2017b). Therefore, we assume that LBs differentiated from iPSCs or ESCs using the "fried egg" method may also have the potential capacity in ARC disease model development.…”
Section: Introductionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) are a member of noncoding RNA and possess a length of over 200 nucleotides, but have no protein-coding potential (5)(6)(7)(8). Many studies show that lncRNA has widely functions in a diversity of biological processes, such as development, cell proliferation, apoptosis and mobility (9)(10)(11)(12)(13). LncRNA has been demonstrated to be involved in the development and progression of various cancers (14).…”
Section: Introductionmentioning
confidence: 99%
“…Long noncoding RNA (lncRNA) have been shown to contribute to cancerous phenotypes such as proliferation, growth suppression, motility, immortality, angiogenesis and viability (Fu et al ., ; Lin et al ., ; Schmitt and Chang, ). Evidence has indicated that lncRNA function primarily through their interactions with cellular macromolecules such as protein, DNA or RNA (Fang et al ., ; Schmitt and Chang, ; Sun et al ., ; Zhang et al ., ).…”
Section: Introductionmentioning
confidence: 99%